European Astrolabes to ca. 1500: An Ordered List - King, David A. (Medieval encounters, 2017)
Research on medieval European astrolabes has hitherto been somewhat haphazard. Most pieces are unsigned and undated, many difficult to assign to a specific region. Some early ones cannot be understood without reference to the Islamic tradition from which they derive. What are perhaps the most important pieces from a historical point of view—the earliest-known astrolabe, from 10th-century Catalonia, and the astrolabe made by the leading astronomer of 15th-century Europe, Regiomontanus,—were declared fakes or suspicious before they could be studied seriously. A detailed study of groups of related instruments, for example, those with Hebrew inscriptions, is a most welcome contribution. A survey of the clearly-identifiable astrolabes made in medieval England (or France or Italy) has never been undertaken; maybe this list might encourage somebody willing to learn the language of instruments to undertake such a task.